On the relationship between incorporation of 32P into phospholipids and binding of beta-adrenoceptor blocking drugs to isolated mast cells - Pecivová, J; Drábiková, K; Jancinová, V; Nosál, R (Agents and actions, 1988)
The lipophilic beta-adrenoceptor blocking drugs exaprolol and propranolol significantly decreased the incorporation of 32P into phosphatidylethanolamine, phosphatidylcholine and phosphatidylinositol of isolated rat mast cells. In contrast, the hydrophilic drugs metipranolol, practolol and atenolol increased the incorporation of 32P into phosphatidylethanolamine, phosphatidylserine and phosphatidylinositol. The inhibition of 32P incorporation by lipophilic drugs correlated with the high binding of these drugs to mast cells.
Keywords: fosfolipidy; Adrenergic beta-Antagonists; krysa rodu Rattus; techniky in vitro; Phosphorus Radioisotopes; Male; radioizotopy fosforu; Animals; Rats, Inbred Strains; beta blokátory; mužské pohlaví; inbrední kmeny potkanů; Phospholipids; In Vitro Techniques; Mast Cells; zvířata; mastocyty; Rats